Effects of Problem-Based Learning (PBL) in Fashion Design Classes - Park, HyeSook (International Journal of Advanced Culture Technology(IJACT), 2019)
In recent years, in order to enhance the problem-solving skills required by the industrial field, universities have introduced the Problem-Based Learning(PBL) method to solve the problems caused by the lack of creativity, problem solving ability and self-directed learning. This study applied PBL class methods such as 'learning based on individual specific problems', 'self-directed learning', and 'small-group learning of small members' to practical design of fashion design. To do this, I conducted a questionnaire after conducting research based on the PBL module for one semester in a practical class of fashion design major at P University. As a result of the survey, the satisfaction and achievement of the class conducted by PBL learning method was improved than the existing teaching method. As such, if PBL class is used as a way of solving problems through close communication between professors and learners, it is expected to be established as a learner-centered education method that can improve creativity and professionalism.